Anti-apoptotic and Neuroprotective Effects of Oxysophoridine on Cerebral Ischemia Both In Vivo and In Vitro - Rui, Chen; Yuxiang, Li; Ning, Jiang; Ningtian, Ma; Qingluan, Zhu; Yinju, Hao; Ru, Zhou; Lin, Ma; Tao, Sun; Jianqiang, Yu (Planta Medica, 2013)
In this study, we investigated the neuroprotective effect of oxysophoridine on ischemia and ischemia-like insults. Protection by oxysophoridine was studied at the in vivo level using a model of middle cerebral artery occlusion in mice and at the in vitro level using primary rat hippocampal neuronal cultures exposed to oxygen-glucose deprivation, a model of ischemia-like injury. The behavioral test was performed by using the neurological scores. The infarction volume of brain was assessed in the brain slices stained with 2,3,5-triphenyl tetrazolium chloride. The neuron apoptosis was evaluated by Hoechst 33342 staining. The morphological change in the neurons was examined using a Transmission Electron Microscope (TEM or EM). To evaluate neuron apoptosis, caspase-3, -9, and − 8 activities were measured using assay kits with an ELISA reader. The Western blotting assay was used to evaluate the release of cytochrome c and expression of caspase-3, Bcl-2, and Bax proteins. The quantitative real-time PCR assay was used to evaluate the release of cytochrome c and the expression of caspase-3 mRNA. Oxysophoridine-treated groups (62.5, 125, 250 mg/kg) markedly reduced neurological deficit scores and infarct volumes. Treatment with oxysophoridine (5, 20, 80 µmol/L) significantly attenuated neuronal damage, with evidence of decreased cell apoptosis and decreased cell morphologic impairment. Furthermore, treatment with oxysophoridine could effectively downregulate the expression of cytochrome c and caspase-3 in both mRNA and protein levels, and Bax in the protein level, and induce an increase of Bcl-2 in the protein level. The caspase-3, -9, and -8 activities were also inhibited. These findings suggested that oxysophoridine may be a potential neuroprotective agent for cerebral ischemia injury.
Keywords: oxysophoridine; cerebral ischemia; middle cerebral artery occlusion; oxygen-glucose deprivation; apoptosis; neuroprotection; Siphocampylus verticillatus; Campanulaceae